1989
DOI: 10.1007/bf00439544
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of 5-HT2 receptors in the regulation of sleep and wakefulness in the rat

Abstract: Recently developed agents specifically acting on different 5-hydroxytryptamine (5-HT) receptor populations were used to analyze the functional role of 5-HT2 receptor subtypes in the sleep-wakefulness cycle of the rat. The 5-HT2 receptor antagonist ritanserin injected intraperitoneally (IP) (0.04-2.5 mg/kg) induced an increase in deep slow wave sleep (SWS2) duration at the expense of wakefulness (W), light slow wave sleep (SWS1) and paradoxical sleep (PS). The stimulation of 5-HT2 receptors by 1-(2,5-dimethoxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(41 citation statements)
references
References 32 publications
7
31
0
3
Order By: Relevance
“…In the present work, we found that the selective blockade of 5-HT 2A receptors by MDL 100907 induced a dose-dependent increase in NREMS in 5-HT 2A ϩ/ϩ mice. Thus, this 5-HT 2A receptor antagonist mimicked the NREMS-promoting action of wide-spectrum 5-HT 2 antagonists, as reported previously in rats and in humans (Dugovic et al, 1989;Idzikowski et al, 1991;Stutzmann et al, 1992).…”
Section: -Ht 2a and 5-ht 2b Receptors Are Involved In Nrems Regulationsupporting
confidence: 81%
See 3 more Smart Citations
“…In the present work, we found that the selective blockade of 5-HT 2A receptors by MDL 100907 induced a dose-dependent increase in NREMS in 5-HT 2A ϩ/ϩ mice. Thus, this 5-HT 2A receptor antagonist mimicked the NREMS-promoting action of wide-spectrum 5-HT 2 antagonists, as reported previously in rats and in humans (Dugovic et al, 1989;Idzikowski et al, 1991;Stutzmann et al, 1992).…”
Section: -Ht 2a and 5-ht 2b Receptors Are Involved In Nrems Regulationsupporting
confidence: 81%
“…Similar results have been obtained in the rat after administration of various 5-HT 2 ligands, whether agonists or antagonists (Dugovic et al, 1989;Kantor et al, 2004) [but see Benington andHeller (1995), in rats, andIdzikowski et al (1991), in human]. These data suggest that the effects of 5-HT 2 ligands on REMS are mediated by complex mechanisms.…”
Section: -Ht 2 Receptors and Remssupporting
confidence: 71%
See 2 more Smart Citations
“…In regard to the present study, 5-HT 1A receptors are located on the soma and dendrites of 5-HT neurons (somatodentritic autoreceptors), as well as postsynaptically on 5-HT target neurons (Kia et al, 1996;Riad et al, 2000). It has been proposed that 5-HT 1A receptors are involved in the regulation of REM sleep and wakefulness (Dzoljic et al, 1992;Tissier et al, 1993;Portas et al, 1996;Thakkar et al, 1998), whereas 5-HT 2A receptors participate in the control of SWS (Idzikowski et al, 1986;Dugovic et al, 1989). The observation that 5-HT 1A null mutant mice have higher amounts of REM sleep than wild-type mice during both the light and dark phases (Boutrel et al, 2002) is consistent with this idea.…”
Section: Physiological Importance Of Serotonergic Inhibitory Input Tomentioning
confidence: 64%